Comparing Elicited Imitation and Word Monitoring as Measures of Implicit Knowledge. Issue 4 (27th September 2015) - Suzuki, Yuichi; DeKeyser, Robert
<x xml:space="preserve">Abstract</x> The present study challenges the validity of elicited imitation (EI) as a measure for implicit knowledge, investigating to what extent online error detection and subsequent sentence repetition draw on implicit knowledge. To assess online detection during listening, a word monitoring component was built into an EI task. Advanced‐level Japanese L2 speakers with Chinese as their native language performed the EI task with the built‐in word monitoring component, a metalinguistic knowledge test, and a probabilistic serial reaction time (SRT) task, which served as a measure of aptitude for implicit learning. Results showed that EI scores were correlated positively with metalinguistic knowledge, but they were not related to the SRT scores. Word monitoring performance, in contrast, was not related to metalinguistic knowledge but correlated positively with SRT scores only among L2 speakers with longer lengths of residence. These results suggest that online error detection can index implicit knowledge, whereas EI may measure automatized explicit knowledge.